Models of Stress in Nonhuman Primates and Their Relevance for Human Psychopathology and Endocrine Dysfunction - Meyer, Jerrold S. (ILAR J, 2014)
Stressful life events have been linked to the onset of severe psychopathology and endocrine dysfunction in many patients. Moreover, vulnerability to the later development of such disorders can be increased by stress or adversity during development (e.g., childhood neglect, abuse, or trauma). This review discusses the methodological features and results of various models of stress in nonhuman primates in the context of their potential relevance for human psychopathology and endocrine dysfunction, particularly mood disorders and dysregulation of the hypothalamic-pituitary-adrenocortical (HPA) system. Such models have typically examined the effects of stress on the animals' behavior, endocrine function (primarily the HPA and hypothalamic-pituitary-gonadal systems), and, in some cases, immune status. Manipulations such as relocation and/or removal of an animal from its current social group or, alternatively, formation of a new social group can have adverse effects on all of these outcome measures that may be either transient or more persistent depending on the species, sex, and other experimental conditions. Social primates may also experience significant stress associated with their rank in the group's dominance hierarchy. Finally, stress during prenatal development or during the early postnatal period may have long-lasting neurobiological and endocrine effects that manifest in an altered ability to cope behaviorally and physiologically with later challenges. Whereas early exposure to severe stress usually results in deficient coping abilities, certain kinds of milder stressors can promote subsequent resilience in the animal. We conclude that studies of stress in nonhuman primates can model many features of stress exposure in human populations and that such studies can play a valuable role in helping to elucidate the mechanisms underlying the role of stress in human psychopathology and endocrine dysfunction.